Tamarind Seeds in Tracheobronchial Tree: Challenges during Rigid Bronchoscopy - Nitinkumar Borkar; Charu Tiwari; C. Ashwin; Kalla Revanth; Ripu Daman Arora; Ranganath Thippanahalli Ganga (Wolters Kluwer Medknow Publications, 2024)
Background: Tamarind seed aspiration is not frequent in children and is usually observed in kids from rural backgrounds, with easy access to tamarind fruits and their by-products. Materials and Methods: We report a retrospective review of five patients managed in the pediatric surgery department for tamarind seed aspiration into the tracheobronchial tree. The data were analyzed based on age, clinical presentation, bronchoscopic observations, and the challenges faced during the rigid bronchoscopic retrieval and postoperative course. Results: There were four boys and one girl with a median age of 10 years. High-resolution computed tomography thorax was done in all patients. The foreign body was identified in the right main bronchus in one and the left main bronchus in four patients. All five patients underwent rigid bronchoscopy and retrieval of the seed. Two patients had an early presentation (within a week) - they needed temporary tracheotomy as the swollen seed could not be negotiated through the narrow glottis. Two patients had a late presentation (around 15 days) - they required removal in piecemeal using crushing forceps and multiple insertions of bronchoscope prolonging surgical time. One patient presented at 22 days posttamarind aspiration. It was soft enough for easy disintegration with crocodile forceps and expeditiously removed in three to four pieces. All patients recovered uneventfully. Conclusion: Removal of tamarind seed foreign body from the tracheobronchial tree is challenging. Anticipating the difficulties and being prepared well, helps to reduce the intraoperative difficulty, and allow successful removal with favorable patient outcomes.